IGCSE cambridge and O level computer science - workbook: Algorithms, programming and logic - Watson, David (London : Hodder education, 2021)
The IGCSE Cambridge and O Level Computer Science Workbook is designed to support students preparing for the Cambridge IGCSE (0478) and O Level (2210) Computer Science syllabuses. It offers a wide range of structured, practical exercises that reinforce understanding of core concepts such as programming, data representation, computer systems, and networks. The workbook complements the main coursebook by providing practice questions, coding tasks (primarily using pseudocode and Python), and exam-style questions to build confidence and exam readiness. It encourages independent learning, logical thinking, and problem-solving skills, aligned with the latest Cambridge syllabus requirements.
Keywords: Computer - text book -- Hodder - Computer - Textbook